Anatomical Structure of Duck Feet and Running Exercise Intensity on the Risk of Musculoskeletal Injuries in Runners in Indonesia: Literature Review - Salsabila Dwi Fitri; Yorasaki Ananta (Siber Nusantara Review, 2024)
The anatomical structure of the foot plays an important role in biomechanical efficiency when running. One of the anatomical variations that is often found is the duck feet condition, which is a position of the feet that points outward when walking or running. This study aims to examine the effect of duck feet and the intensity of running training on the risk of musculoskeletal injuries in runners, especially in Indonesia. The method used is a literature review of various relevant national and international journals in the last 5 years. The results of the study indicate that duck feet posture can cause biomechanical imbalances that increase pressure on the knee, ankle, and lower back joints, and contribute to the risk of recurrent injury. Meanwhile, excessive training intensity without proper control also exacerbates the risk of injury. A better understanding of the foot structure and training intensity settings is needed from coaches, physiotherapists, and runners to prevent long-term musculoskeletal injuries.